IMPLEMENTASI PENANAMAN KESADARAN PENTINGNYA KETERAMPILAN SOFT SKILLS ENTREPRENEURSHIP WADAH PENGEMBANGAN FKIP UNBARI - Harbeng Masni; Ade Rahima; Zuhri Saputra Hutabarat (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Implementation of Instilling Awareness of the Importance of Soft Skills Entrepreneurship Through Student Development FKIP UNBARI